2012
DOI: 10.1016/j.bbrc.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine B10 triggers a heme propionate hydrogen bonding network loop with glutamine E7 moiety

Abstract: Propionates, as peripheral groups of the heme active center in hemeproteins have been described to contribute in the modulation of heme reactivity and ligand selection. These electronic characteristics prompted the question of whether the presence of hydrogen bonding networks between propionates and distal amino acids present in the heme ligand moiety can modulate physiological relevant events, like ligand binding association and dissociation activities. Here, the role of these networks was evaluated by NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The signature Arg or His residue is responsible for the hydrogen bonding with one heme propionate (Otyepka et al, 2007). It has been suggested that these hydrogen bonds not only can influence the stability of hemeproteins, but also their reactivity and ligand selection (Ramos-Santana and Lopez-Garriga, 2012). Note that Gln is also able to generate a hydrogen bond with the heme propionate.…”
Section: Discussionmentioning
confidence: 99%
“…The signature Arg or His residue is responsible for the hydrogen bonding with one heme propionate (Otyepka et al, 2007). It has been suggested that these hydrogen bonds not only can influence the stability of hemeproteins, but also their reactivity and ligand selection (Ramos-Santana and Lopez-Garriga, 2012). Note that Gln is also able to generate a hydrogen bond with the heme propionate.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S Exiting the Heme Pocket and the H-Bond Network in Ferric HbI. Several side chains within the distal pocket of HbI are involved in a hydrogen bond network, 33,41 especially Gln(E7), whose mutation alters the properties of the protein. 10 The kinetic parameters of H 2 S geminate rebinding are changed upon mutation of Gln(E7) (Table 1): the proportion of H 2 S released into solution is increased for the Gln(E7)Val mutant (29%) but decreased substantially for the Gln(E7)His mutant (5%).…”
Section: ■ Discussionmentioning
confidence: 99%
“…This six-coordinate excited species decays to the ground state with a time constant (5.8 ps) similar to that observed in the case of the O 2 sensor Dos 42 and very close to that of the truncated hemoglobin Mt-TrHbO 44 and the O 2 sensor FixL (4.7 ps), 42 for which no heme doming is observed after photoexcitation. 43 The 5.8 ps time constant, first assigned to O 2 geminate rebinding in the O 2 sensor DOS, 41 was latter reassigned to the six-coordinate vibrationally excited heme− O 2 complex on the basis of time-resolved Raman spectra, 43 a transient species that is induced by the trapping of O 2 by hydrogen bond(s) in a configuration still interacting with Fe 2+ . Consequently, only O 2 that rebinds with a τ gem of 100 ps corresponds to geminate rebinding stricto sensu, and the quantum yield for O 2 dissociation is much lower for the HbII/ III−O 2 complex than for the HbI−O 2 complex.…”
Section: ■ Discussionmentioning
confidence: 99%